Validity and reliability of the My Jump 2 app for detecting interlimb asymmetry in young female basketball players - Stojiljković, Nenad; Stanković, Dušan; Pelemiš, Vladan; Čokorilo, Nebojša; Olanescu, Mihai; Peris, Miruna; Suciu, Adrian; Plesa, Alin (Frontiers in Sports and Active Living, 2024)
The aim of this study was to examine validity and reliability of My Jump 2 app for the assessment of interlimb jump asymmetry in young female basketball players. Nine athletesAthletes (age 15 (0.9) y; weight 62.9 (5.8) kg; height 173.6 (6.1) cm performed single leg drop jumps (DJ) and both legs drop jumps on force plate (Kistler Quattro jump) force plate and were simultaneously recorded on two smartphones using My Jump 2 app. Jump height from flight time and contact time data was statistically analyzed to evaluate validity of two different camera settings, drop jump performance and interlimb jump asymmetry in basketball players. The reliability was repeated after one week. High test-retest reliability (ICC > 0.88) was observed in DJ (Drop jump) height. High correlation bBetween force plate and My Jump 2 app were observed in, DJ height (r = 0.99) and DJ contact time (r = 0.98). For the inter-limb jump height asymmetries, values mean differences were 0.65.7 and 6.3 percentages for the My Jump 2 app and the force plate, respectively (p = 0.77). Interdevice reliability reveal almost perfect correlation for the DJ height (ICC = 0.99, r = 0.98). The My Jump 2 app is a valid tool to assess drop-jump performance and interlimb asymmetry in young female basketball players.